(untitled) (International Journal of Mathematics and Physics, 2015)
In this work programming of physical agents using the designer of Lego was carried out. The main opportunities with the description of omponents of the the creating robot designer were lit. The robot finding the road was experimentally created and the effective algorithm of its programming is chosen. Methods of training in bases of programming of robots using the above-named designers are shown to students. The RobotC environment as means of programming with examples of works of automation and management of physical agents in real time was used. Functionality of this environment the very wide. Environment gives the chance to program physical robots by a traditional method. The student seized effective algorithms of control of the robot finding the road and also enhanced skills on search of methods of modulation, optimum control of agents. As a result of work the student showed also other capabilities to solve complex engineering challenges.